GA-based optimization for integration of DGs, STATCOM and PHEVs in distribution systems - Bindeshwar Singh; Swati Singh (Energy Reports, 2019)
This paper presents a Genetic Algorithms (GAs) for integration of various types of Distributed Generations (DGs), Static Synchronous Compensator (STATCOM) and Plug-in-Hybrid Electric Vehicle (PHEVs) with different static load models (DSLMs) such as LM-1, LM-2, LM-3, LM-4 and LM-5, respectively in distribution systems from minimization of total real power loss of the system viewpoint. In this analysis, the system power factor taken as power system performances in various cases such as without DGs, with various types of DGs, integration of DGs and STATCOM, integration of DGs, STATCOM and PHEVs in distribution system with DSLMs. The proposed methodology has been tested for IEEE-37 bus distribution test system. This research work is very much useful for researchers, scientific, industrial, academicians and practitioners for whose are working in the fields of integration of renewable energy sources, FACTS controllers and PHEVs in distribution systems with DSLMs from minimization of total real power loss of the system viewpoint. This research work also is useful for practical implementations of integration of renewable energy sources, FACTS controllers and PHEVs in distribution systems with DSLMs for enhancement of different power system performances from minimization of total real power loss of the system viewpoint.
Keywords: 330; Distributed Generations (DGs); Distribution systems; Genetic Algorithms (GAs); Location and size; Plug-in-Hybrid Electric Vehicle (PHEVs); Static Synchronous Compensator (STATCOM)